The Myth of Consciousness: The Reality of Brain-Sign - Clapson, Philip (Journal of NeuroPhilosophy, 2022)
The physical sciences, as generally understood, are disciplines concerned with the characteristics and behavior of physical objects and states. What is evident about the current condition of consciousness is that: 1) It has no identified physical states; 2) There is no generally accepted vocabulary of its functioning, or its participant entities; and 3) No ‘normal science’ operative structure upon which a community of scientists agree (ref. T. Kuhn). The reasons are that consciousness is a prescientific concept persisting because there is no adequate physicalist theory to replace it, and because biology operates in a way ‘invisible’ to assumed mental processes and vocabulary. What is required is a plausible theory built on a biophysical base. A theory is being developed: it is termed the theory of brain-sign. Brain-sign replaces consciousness as an evolved neural operation in which brains communicate with each other in the collective action of organisms, so addressing the limitations of being an isolated individual. It depends upon neural signification (as brain-sign), in this case of the organisms’ immediate causal orientation towards the world. Thus, multiple organisms are linked as one biophysical operation. Signs are biologically ubiquitous and inherently physical. Organisms are not subjective agents with transcendent (quasi-divine) powers acting in a perceivable world, but evolved organic objects with the ability to cooperate as one overarching biological process. It is anticipated this theoretical operation and vocabulary will explain brain function, which mind fails to do. It accounts for science from both its neural origins and its communal nature.